Development, characterization, and storage stability of squash candy bars - Tan, Lucille Alamis (2002.)
Five formulations of squash candy bars were prepared by varying the amounts of both the coconut milk and evaporated milk which were incorporated into the product.
Thesis - B.S. (Food Technology) - SOTECH, University of the Philippines in the Visayas.
Keywords: Squashes; Candy bar